Growth Arrest-Specific 6 (Gas6) and TAM Receptors in Mouse Platelets - BİNGÖL ÖZAKPINAR, ÖZLEM (GALENOS YAYINCILIK, 2015)
Objective: Growth arrest-specific 6 (Gas6) is a newly discovered vitamin K-dependent protein, which is a ligand for TAM receptors [Tyro3 (Sky), Axl, and Mer] from the tyrosine kinase family. Gas6 knockout mice were resistant to venous and arterial thrombosis. There are contradictory reports on the presence of Gas6 and its receptors in mouse platelets. The objective of this study was to investigate whether Gas6 and its receptors were present in mouse platelets or not. Materials and Methods: Specific pathogen-free BALB/c male and female mice of 8-10 weeks old and 25-30 g in weight were anesthetized under light ether anesthesia and blood samples were taken from their hearts. RNAs were isolated from isolated platelets, and then mRNAs encoding Gas6 and TAM receptors were detected by reverse transcription-polymerase chain reaction (RT-PCR). Protein concentrations of Gas6 and TAM receptors in platelets were measured by ELISA, but not those of Mer, because of the absence of any commercial ELISA kit for mouse specimens. Results: RT-PCR results indicated the presence of mRNAs encoding Gas6 and Mer in mouse platelets. However, although RTPCR reactions were performed at various temperatures and cycles, we could not detect the presence of mRNAs encoding Axl and Tyro3 (Sky). Receptor protein levels of Axl and Tyro3 were below the detection limits of the ELISA method. Conclusion: We found the presence of mRNAs encoding Gas6 and the receptor Mer in mouse platelets, but not Axl and Tyro3. Gas6, Axl, and Tyro3 protein levels were below the detection limits of the ELISA. The presence of mRNA is not obvious evidence of protein expression in platelets that have no nucleus or DNA. Further studies are required to clarify the presence of Gas6/TAM receptors in platelets using real-time PCR and more sensitive immunological methods, and future studies on mechanisms will indicate whether the Gas6/TAM pathway is a strategy for treatment of disorders.
Keywords: Blood platelets; Growth arrest-specific protein 6; Hemostasis; VASCULAR SMOOTH-MUSCLE; TYROSINE KINASE; PROTEIN-S; EXPRESSION ANALYSIS; BLOOD-COAGULATION; ENDOTHELIAL-CELLS; AXL; GENE; MER; LIGAND